ISRAEL AND PALESTINE CONFLICT FROM LINGUISTICS AND FIQH SIYASAH PERSPECTIVE - Abdul Mutaali Ahmad (AHKAM : Jurnal Ilmu Syariah, 2018)
This research is based on the linguistic design of religious texts with diplomatic solutions to the Israeli-Palestinian conflict based on the perspective of Fiqh Siyasah .. Since the conflict of these two nations in 1947 to the present day, in the geopolitical context that the solution of the presence of peace in these two regions is to equate the international perception to this conflict as a mediator. The reason is that there is an alignment with linguistic design on the text of the Qur'anic verse which always' uses a plural form . Interestingly, the number of Jews in the world is 15 million, compared with Indonesia 250 million people, but the Qur'an never uses pronouns for Jews as a minority group or even always mentioned the majority. In the Siyasah fiqh , if this happens may take several alternatives; priority and Sad Dzari'ah benefit . . Sources of data used are the Qur'an and the hadith of the prophet. The method used in this research is to analyze bibliography data with content analysis approach . The study concludes that there are differences in text and context in the efforts to resolve the Israeli-Palestinian conflict and the two-state peace solution.